The clinical method in primary health care: some reflections - Rubén Darío García Núñez (Medisur)
A bibliographical review on the importance of the clinical method in the primary health care was carried out. This method is composed by a system of rules that organize the procedures the doctor follows in order to obtain the symptoms and signs that will allow him to elaborate a further diagnosis. Different issues like the importance of the medical diagnosis, its bases, the different procedures through which it can be carried out, and how it is finally established are stated. The paper also analyzes the different diagnostic hypotheses, the importance of technology for the medical diagnosis, and the link between clinic and technology. Some peculiarities of the diagnosis in the primary health care, as well as its vulnerabilities and main deficiencies that affect the teaching of this medical sciences method are also exposed.